A novel transport assimilation method for the Atlantic meridional overturning circulation at 26°N. (25th February 2014) - Hermanson, Leon; Dunstone, Nick; Haines, Keith; Robson, Jon; Smith, Doug; Sutton, Rowan
<x xml:space="preserve">Abstract</x> One of the prerequisites for achieving skill in decadal climate prediction is to initialize and predict the circulation in the Atlantic Ocean successfully. The RAPID array measures the Atlantic Meridional Overturning Circulation (MOC) at 26°N. Here we develop a method to include these observations in the Met Office Decadal Prediction System (DePreSys). The proposed method uses covariances of overturning transport anomalies at 26°N with ocean temperature and salinity anomalies throughout the ocean to create the density structure necessary to reproduce the observed transport anomaly. Assimilating transport alone in this way effectively reproduces the observed transport anomalies at 26°N and is better than using basin‐wide temperature and salinity observations alone. However, when the transport observations are combined with in situ temperature and salinity observations in the analysis, the transport is not currently reproduced so well. The reasons for this are investigated using pseudo‐observations in a twin experiment framework. Sensitivity experiments show that the MOC on monthly time‐scales, at least in the HadCM3 model, is modulated by a mechanism where non‐local density anomalies appear to be more important for transport variability at 26°N than local density gradients.